THE INFLUENCE OF COMPETENCY FACTORS, CAREER DEVELOPMENT AND MOTIVATION ON PERSONNEL PERFORMANCE - Eko Kurniawan; Adi Bandono; As'ad Aris M (STTAL POSTGRADUATE - INTERNATIONAL CONFERENCE, 2020)
Organizational goals will be achieved through positive employee performance, otherwise the organization will face obstacles in achieving goals when employee performance is ineffective, so that the success of an organization will be greatly influenced by the performance of its employees. The problem in this study is how to determine the effect of motivation, competence and career development of a person on employee performance. While the purpose of this study was the method used in this research is quantitative method using Structural Equation Modelling (SEM) analysis techniques, to find out the influence relationship between the variables studied. The results showed that the competence of employees on employee performance is significant. This means that the more competent an employee is, the more positive his performance will be, as well as career development for employees has a positive effect on improving employee performance. Competency level and employee career development have a positive effect on employee motivation and also affect employee performance improvement. Keywords : Competence, Career Development, Motivation, Employee Performance, Structural Equation Modelling (SEM)